Methane adsorption characteristics of copper oxide modified NaY zeolite adsorbents - K. S. N, Kamarudin (Academy of Sciences Malaysia, 2010)
Ordered microporous NaY zeolite and mesoporous copper oxide are high performance material as catalysts and adsorbents. The copper oxide-NaY zeolite modification in combination of their physicochemical properties could provide excellent opportunities for the creation of new gas adsorbents. In this study, modified NaY zeolite properties and methane adsorptive characteristics were investigated by dispersing copper oxide onto the NaY zeolite structure using the thermal dispersion method. The structures of the copper oxide modified zeolites were characterized by powder X-ray diffraction and Micromeritics ASAP 2000, while the methane adsorption characteristics were analyzed using a thermogravimetric analyzer. The results revealed that types of copper oxide, copper oxide loading concentration, calcination temperature and calcination time greatly affected the modified zeolite structure and gas methane adsorption characteristics.